Strengthening Halal Lifestyle Behavior Literacy in Stunting Prone Communities - Dewi Agustina; Chuzaimah Batubara; Tri Niswati Utami (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
The community including the government, practitioners, and academics have not paid attention to the urgency of halal lifestyle in solving health problems such as malnutrition and stunting. This article aims to explain the strengthening of community literacy about halal lifestyle behavior to prevent stunting. Activities began August - October 2023 in Bandar Sono Village, Nibung Hangus District, Batu Bara Regency. Data were collected through focus group discussions (FGDs), and then education and mentoring were carried out. Data from FGDs were analyzed using ATLAS.Ti23. The data obtained was continued by conducting education and mentoring. The results of data processing are then displayed in tables and figures. The findings show that halal lifestyle behavior has not been understood by the community. Ethical and social moral principles include 5 aspects of halal life style behavior that can be applied by humans in living their daily lives so as to provide a strong impetus to maintain nutritional balance, avoid harmful behavior, and provide better care for children. This means that hifz ad din (protecting religion), as part of halal life style behaviors, is not a direct method of preventing stunting, however, it creates a strong foundation for healthy behaviors and careful care of children, which in turn can contribute to stunting prevention. A person's knowledge will become broad if he learns a lot and gets information through school or information provided through counseling, lectures, reading. The local government needs to continuously provide assistance to families prone to stunting by involving religious leaders so that the community has a strong foundation for implementing halal lifestyle behavior.